WAYS TO IMPROVE STUDENTS’ PRACTICAL SKILLS MASTERING IN THE COURSE OF MEDICAL BIOLOGY STUDY - Швець, Л. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The ways to improve students’ practical skills mastering in the course of Medical Biology study were analyzed in order to effectively transform theoretical knowledge into experience and to form clinical thinking of future specialists. Students’ mastering of practical skills is divided into two stages: during the current practical class and during final module controls. The primary condition for the formation of professional abilities and skills is proper financial support with microscopes, microslides and gross specimens. There are TV sets in all classrooms providing an opportunity to use fragments of films about the sequence of the basic techniques of genetic and parasitological research mastering combined with the demonstration of corresponding clinical situations. Students’ ability to get acquainted with the peculiarities of work in genetic laboratories promotes better assimilation of practical skills and abilities in Medical Genetics. The department staff has developed a list of practical skills and algorithms for their implementation. Instructions for step-by-step performing of specific tasks are presented in study guides, study manuals, study albums. Students’ independent work under the teacher’s supervision, the use of modern educational technologies (business simulations), individual approach to the formation of practical skills and abilities are assessed according to the developed score scale. The motivation to master practical skills involves inclusion of their assessment into the overall number of points at practical classes and final module controls. If students get a positive mark for their practical skills, they get about 30% of points at each of the three final module ontrols. Thus, in the course of Medical Biology study students master practical skills with the use of methodological support, precise algorithms of practical skills and their assessment criteria at each current practical class and final module control according to the developed scores scale.